2019
DOI: 10.1002/lary.28465
|View full text |Cite
|
Sign up to set email alerts
|

Role of epstein‐barr virus in the severity of recurrent respiratory papillomatosis

Abstract: The objective was to investigate the prevalence of the Epstein-Barr virus (EBV) and its association with human papilloma virus (HPV) detection, clinicopathological features, and the severity of recurrent respiratory papillomatosis (RRP). Methods: Cases of juvenile recurrent respiratory papillomatosis (JRRP) (n = 36) and adult recurrent respiratory papillomatosis (ARRP) (n = 44) were collected retrospectively and subdivided into low-and high-risk severity groups based on the Derkay score. We performed HPV detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Among these patients, we previously reported that JORRPs were significantly more aggressive (mean Derkay score of 10.9) than AORRP cases (mean Derkay score of 8.2; p = .02), 24 and that the presence of Epstein-Barr was not associated to progression/severity of RRP. 25 Molecular variants of HPVs 6 and 11 were here characterized based on the nucleotide sequence of segments of the viral genome that enclose sufficient single nucleotide polymorphisms to discriminate between major viral lineages and sublineages. 14,15 We observed predominance of HPV-6 B1 and B3 variants with some nonsignificant differences in their distribution: specifically, HPV-6 B1 variants were detected in higher frequency among JORRP cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, we previously reported that JORRPs were significantly more aggressive (mean Derkay score of 10.9) than AORRP cases (mean Derkay score of 8.2; p = .02), 24 and that the presence of Epstein-Barr was not associated to progression/severity of RRP. 25 Molecular variants of HPVs 6 and 11 were here characterized based on the nucleotide sequence of segments of the viral genome that enclose sufficient single nucleotide polymorphisms to discriminate between major viral lineages and sublineages. 14,15 We observed predominance of HPV-6 B1 and B3 variants with some nonsignificant differences in their distribution: specifically, HPV-6 B1 variants were detected in higher frequency among JORRP cases.…”
Section: Discussionmentioning
confidence: 99%
“…Age at onset was the only significant risk factor for aggressive disease in JO-RRP, whereas in adults, both HPV11 and observation time ≥10 years were significant [ 64 ]. In a series by Costa et al (2019), 36 patients with JO-RRP and 44 patients AO-RRP were subdivided into low- and high-risk groups based on Derkay scores [ 71 ]. HPV6 detection was significantly higher in AO-RRP cases ( p = 0.03), whereas HPV11 was more prevalent in JO-RRP cases ( p = 0.02), and even more prevalent in high-risk JO-RRP cases (Derkay laryngoscopic scale ≥ 20) ( p = 0.04) [ 71 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)mentioning
confidence: 99%
“…In a series by Costa et al (2019), 36 patients with JO-RRP and 44 patients AO-RRP were subdivided into low- and high-risk groups based on Derkay scores [ 71 ]. HPV6 detection was significantly higher in AO-RRP cases ( p = 0.03), whereas HPV11 was more prevalent in JO-RRP cases ( p = 0.02), and even more prevalent in high-risk JO-RRP cases (Derkay laryngoscopic scale ≥ 20) ( p = 0.04) [ 71 ]. Similar results were published by Nogueira et al (2021), who found that age of onset of RRP had an important impact on the number of surgeries needed to control the disease.…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)mentioning
confidence: 99%
“…Juvenile onset recurrent respiratory papillomatosis (JoRRP) is a rare and challenging HPV-induced disease, frequently associated with mucosal HPV-type infection, in particular HPV 6 and 11, and characterised by the growth of squamous papillomata in the airway epithelium [ 1 ]. It is defined by the onset before 12 years of age with the peak of incidence being commonly before 5 years [ 2 ]. Because of JoRRP’s typical recurrence, patients often require multiple surgical debulking procedures to maintain an airway patency [ 3 ].…”
Section: Introductionmentioning
confidence: 99%